2020
DOI: 10.1021/acs.analchem.0c02938
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Pressure Ion Funnel: Concepts, Simulations, and Analytical Performance

Abstract: In mass spectrometry (MS), a major loss of ions can readily occur during their transfer from atmospheric pressure to a lower pressure, which limits performance. Here, we report an ion funnel that can be used to effectively focus ions at ambient pressure (∼777 Torr) to significantly enhance performance in electrospray ionization (ESI) MS. For seven singly charged test ions (m/z 124− 1131), the ambient pressure ion funnel (APIF) is demonstrated to improve ion abundances, sensitivity, and detection limits by up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Our group recently reported an ambient pressure ion funnel (APIF) that attaches to the capillary entrance of a commercially available MS to increase the sensitivity of electrospray ionization MS by up to ∼16 fold when compared to the ‘standard’ operation of ESI-MS without the APIF. 26 Thus, the integration of APIF with DMS should also be useful for enhancing the ion transmission efficiency of high resolution DMS-MS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently reported an ambient pressure ion funnel (APIF) that attaches to the capillary entrance of a commercially available MS to increase the sensitivity of electrospray ionization MS by up to ∼16 fold when compared to the ‘standard’ operation of ESI-MS without the APIF. 26 Thus, the integration of APIF with DMS should also be useful for enhancing the ion transmission efficiency of high resolution DMS-MS.…”
Section: Introductionmentioning
confidence: 99%
“…27 In particular, the ion trajectory simulation software SIMION has been used for simulating both DMS and APIF instrumentation. 26,28–30 For example, Prasad et al 31 developed a SIMION-based DMS model to enable the accurate prediction of experimental CV values, peak width and ion current for a microscale DMS device. Tang et al 32 used SIMION to develop a DMS model that was shown to experimentally improve the resolution of microscale DMS by focusing ions before entering DMS separation region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Before entering the mass analyzer, the ions need to pass through the sub-vacuum pre-stage chamber, where the movement of ions is strenuous. An ion funnel can improve ion transmission efficiency, focusing the moving ions radially 21 and reducing ion loss. [22][23][24] Besides, ion transmission efficiency can be improved by using a supplemental electron source inside the skimmer.…”
Section: Introductionmentioning
confidence: 99%
“…35 Ambient-pressure ion funnel systems have also been developed to enhance the transmission of ions. 36,37 Nonetheless, further improvement in the ion current from a single emitter is limited by the smallest droplet size that can be generated at a given flow rate and the maximum amount of charge carried by the ESI droplets, which is known as the Rayleigh limit. 38−40 Multiplexing of the ESI emitters is a promising strategy that has been employed to overcome this limitation.…”
Section: ■ Introductionmentioning
confidence: 99%